Practical Application of QR Code Electronic Manuals in Equipment Management and Training - Ma, Lifang; Mu, Yonghong; Wei, Ling; Wang, Xiumei (Frontiers in Public Health, 2021)
Objective: To explore the application value of QR code electronic manuals in operating theatre equipment management and training. Methods: The control group adopted the traditional management mode. Training was carried out before each device was put into use in the department. A unified operation process and a paper card manual for common faults were formulated and hung next to each device. For the observation group, the electronic manuals generated by the QR code were pasted on the operating theatre equipment for management and training. The management and training effect was compared between the two groups. Results: The efficiency of equipment management and training using the QR code electronic manuals was significantly higher than that of traditional training, and the difference was statistically significant (P < 0.05). Conclusion: The QR code manuals are very effective in operating theatre equipment management and training. They can be read and learned in time to improve the operating theatre equipment utilisation rate, accuracy rate and equipment management and training quality.